2022
DOI: 10.1002/er.8612
|View full text |Cite
|
Sign up to set email alerts
|

Coffee silverskin as a substrate for biobased production of biomass and hydrogen by Escherichia coli

Abstract: Currently, coffee consumption reached 9.92 million tons, being responsible for the generation of huge amounts of waste associated with coffee bean processing steps and further operations. Coffee silverskin (CS) and spent coffee grounds having high organic content are generated as a result of roasting and brewing processes. Escherichia coli wild-type and septuple mutant (ΔhyaB ΔhybC ΔhycA ΔfdoG ΔldhA ΔfrdC ΔaceE) growth and hydrogen production were investigated in mediums containing 20 to 200 g L À1 CS with dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Previous studies have also reported the production of bio-butanol from coffee silverskins. However, the use of coffee silverskin and SCGs for bio-butanol production can be prohibitively difficult, especially when compared to other raw lignocellulosic materials, which are widely available in large amounts [65,66]. Additionally, bio-H 2 production of coffee silverskin using E. coli with the yield of 2.15 mL/g raw coffee silverskin was reported by Trchouian group [67,68].…”
Section: Coffee Silverskinmentioning
confidence: 99%
“…Previous studies have also reported the production of bio-butanol from coffee silverskins. However, the use of coffee silverskin and SCGs for bio-butanol production can be prohibitively difficult, especially when compared to other raw lignocellulosic materials, which are widely available in large amounts [65,66]. Additionally, bio-H 2 production of coffee silverskin using E. coli with the yield of 2.15 mL/g raw coffee silverskin was reported by Trchouian group [67,68].…”
Section: Coffee Silverskinmentioning
confidence: 99%